2009
DOI: 10.1177/0961203308094559
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-18 promoter polymorphisms with WHO pathological classes and serum IL-18 levels in Chinese patients with lupus nephritis

Abstract: Accumulating evidence indicates that interleukin (IL)-18 has a central role in the pathogenesis of lupus nephritis (LN). Although two recent studies showed that IL-18 promoter gene polymorphisms might be associated with systemic lupus erythematosus (SLE), to our knowledge, there have not been any reports concerning their association with LN. The aim of our study was to investigate the association of IL-18 promoter polymorphisms with World Health Organization pathological classes and identify their functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Our data were consistent with recent results that showed lupus patients with AA genotype had significantly lower IL-18 levels than those with the CC and CA genotypes 29,31 . Comparison of promoter polymorphisms of IL-18 gene with sequences in the TRANSFAC (Gene Transcription Factor) database suggest that the change from C to A at position -607 possibly disrupts a potential CREBP binding site and may reduce IL-18 production 23 .…”
Section: Rheumatologysupporting
confidence: 96%
“…Our data were consistent with recent results that showed lupus patients with AA genotype had significantly lower IL-18 levels than those with the CC and CA genotypes 29,31 . Comparison of promoter polymorphisms of IL-18 gene with sequences in the TRANSFAC (Gene Transcription Factor) database suggest that the change from C to A at position -607 possibly disrupts a potential CREBP binding site and may reduce IL-18 production 23 .…”
Section: Rheumatologysupporting
confidence: 96%
“…LPS and TNF did not increase IL-18 mRNA levels while the production of proIL-18 and, especially, mature IL-18 was markedly enhanced in response to stimulation, suggesting that posttranscriptional processing was responsible for the up-regulation of renal IL-18 during the progression of lupus nephritis [15]. Latest two studies showed that promoter polymorphism inXuenced expression of IL-18 [20,21]. Moreover, one latest Spanish study conWrmed an important role of the novel IL18 rs360719 variant in determining the susceptibility to SLE [22].…”
Section: Discussionmentioning
confidence: 97%
“…Two single nucleotide polymorphisms (A-607C and G-137C) in the promoter region of the IL-18 gene have been found repeatedly to be associated with the IL-18 promoter transcription activity (Khripko et al, 2008;Chen et al, 2009). We attempted to elucidate the inherited basis of the differences among individual responses to the drugs association with cytokine genetic background, so as to identify the right dose of tacrolimus for each recipient.…”
Section: Introductionmentioning
confidence: 99%